Engineering a Multifunctional Nitroreductase for Improved Activation of Prodrugs and PET Probes for Cancer Gene Therapy. Issue 3 (16th March 2017) - Copp, Janine N.; Mowday, Alexandra M.; Williams, Elsie M.; Guise, Christopher P.; Ashoorzadeh, Amir; Sharrock, Abigail V.; Flanagan, Jack U.; Smaill, Jeff B.; Patterson, Adam V.; Ackerley, David F.
Summary: Gene-directed enzyme-prodrug therapy (GDEPT) is a promising anti-cancer strategy. However, inadequate prodrugs, inefficient prodrug activation, and a lack of non-invasive imaging capabilities have hindered clinical progression. To address these issues, we used a high-throughput Escherichia coli platform to evolve the multifunctional nitroreductase E. coli NfsA for improved activation of a promising next-generation prodrug, PR-104A, as well as clinically relevant nitro-masked positron emission tomography-imaging probes EF5 and HX4, thereby addressing a critical and unmet need for non-invasive bioimaging in nitroreductase GDEPT. The evolved variant performed better in E. coli than in human cells, suggesting optimal usefulness in bacterial rather than viral GDEPT vectors, and highlighting the influence of intracellular environs on enzyme function and the shaping of promiscuous enzyme activities within the "black box" of in vivo evolution. We provide evidence that the dominant contribution to improved PR-104A activity was enhanced affinity for the prodrug over-competing intracellular substrates. Graphical Abstract: Highlights: E. coli NfsA was evolved for improved activation of the anti-cancer prodrug PR-104A Co-activation of two PET-imaging probes and metronidazole was also enhanced Improved activity was more evident in the E. coli evolutionary host than human cells Evading competing metabolites can drive evolution of promiscuous enzyme activities Abstract : Copp et al. used directed evolution to improve activation of the clinically advanced prodrug PR-104A by nitroreductase NfsA, with concurrent improvement in co-activation of PET-imaging probes and metronidazole enhancing non-invasive imaging potential and providing a safety switch for cancer gene therapy.